Trust and the United Nations Global Compact: A Network Theory Perspective. (March 2013) - Gilbert, Dirk Ulrich; Behnam, Michael
The United Nations Global Compact (UNGC) is a Global Public Policy Network supporting ten universal principles in the areas of human rights, labor standards, environmental protection, and anticorruption. Networks such as the UNGC are an organizational form with distinct structural properties and specific requirements regarding coordination. Relationships among network partners are typically complex, reciprocal, and trust based. Despite the relevance of trust for a successful coordination of networks, the literature on the UNGC remains relatively silent when it comes to this phenomenon. The conditions and mechanisms that contribute to the constitution of trust in the UNGC are poorly understood. Based on research in network theory, the authors argue that the trust of participants and other stakeholders supporting the UNGC is a key precondition to enhance collaboration and to further develop the initiative. Against this background, the aim of this article is to develop a systematic approach to foster the constitution of trust in the UNGC. A thorough investigation of the connection between trust and the UNGC may help identify concrete measures for increasing the scale and scope of collaboration between stakeholders and stimulating not only collective learning but also the implementation of the Global Compact's ten principles.